Visceral and serum lysozyme activities in some freshwater fish (three catfish and two carps) - Panase P. (2017)
© 2016, Springer-Verlag London. The lysozyme activities were investigated in three catfish: hybrid catfish [Clarias macrocephalus (Günther 1864) x Clarias gariepinus (Burchell 1822)], Hemibagrus filamentus (Fang and Chaux 1949), and Kryptopterus apogon (Bleeker 1851) and two carps: Oreochromis niloticus (Linnaeus 1758) and Channa striata (Bloch 1793). Fish samples used in this study were from two sites of Chiang Mai province; C. macrocephalus x C. gariepinus and O. niloticus were from Ton Payom Market, Amphoe Muang. H. filamentus, K. apogon, and C. striata were from Doi Tao Lake, Amphoe Doi Tao. The serum, brain, liver, and kidney of the catfish and carps from both sites were spectrophotometrically measured at 450 nm by ELISA reader. C. macrocephalus x C. gariepinus and H. filamentus showed the highest lysozyme activity in the serum, followed by the kidney, brain, and liver, respectively, while the highest lysozyme activity was observed in the brain of K. apogon, and the least one was observed in the liver. Among the catfish, lysozyme activities of K. apogon were significantly higher than those of the other fish (P  <  0.01). However, no significant difference in lysozyme activity from the three investigated visceral organs was found. In carps, O. niloticus had the highest lysozyme activity in the serum, followed by the kidney, brain, and liver, respectively. Meanwhile, the highest lysozyme activity in C. striata was recorded in the serum, followed by the liver, brain, and kidney. However, there was no significant difference in lysozyme activity from the serum and the internal organs in these two fish. In conclusion, the innate immunity arms in these five fish species encompassed the similar function pattern, although they were differently present in their organs. The data will be used as reference ranks for these species to evaluate health status when they are exposed to some pathogens or chemical contamination in streams and reservoirs.